Analisis Kadar Senyawa Flavonoid Ekstrak Etanol Buah Pare (Momordica charantia L.) - Tri Suci Lestari; Baharuddin Hamzah (Media Eksakta, 2022)
Pare (Momordica charantia L.) is a plant that grows in the tropics, namely Asia, the Amazon (South America), East Africa and the Caribbean. The bitter taste of this fruit gives rise to several benefits including stimulating appetite, curing jaundice, improving digestion. Bitter taste in bitter melon is caused by the content of momordicosides of the triterpene glucoside group or kukurtibacin. This study aims to determine the levels of flavonoids in bitter melon (Momordica charantia L.). The method used in this research is the maceration extraction method using ethanol as a solvent. The extraction results were analyzed qualitatively by adding Mg and HCl powder to determine the presence of flavonoid compounds. While the quantitative test was carried out using the differential pH method in an acidic atmosphere, namely at pH 1 and pH 4.5. Determination of flavonoid content of bitter melon extract using UV-Vis spectrophotometry at 520 nm and 700 nm wavelengths. The results obtained in the qualitative test showed that the bitter melon extract contained positive flavonoids. The results of the quantitative test showed that the total flavonoid content in the bitter melon extract was 0.41 mg/100 g.